Olmesartan-induced collagenous sprue - Freeman, Hugh James (International journal of celiac disease, 2020)
A 65-yr-old female with diarrhea for 3 months and weight loss was evaluated. There was no travel or family history, but she had been treated with olmesartan for an elevated blood pressure. Fecal studies for an infectious cause were negative and serological studies for celiac disease were negative. A small bowel biopsy showed changes of collagenous sprue. The drug was discontinued. Diarrhea ceased and she regained her weight. Repeat biopsies of the small bowel were normal. Except for cessation of the olmesartan, no other dietary (eg., gluten-free diet) or treatment medication (eg., steroids) was provided. Long-term follow-up revealed no recurrence of symptoms in patients with sprue-like intestinal disease or collagenous sprue, consideration should be given to a drug-induced cause. This may limit the need for further clinical studies, restrictive diets or powerful prescribed medications, including steroids and immunosuppressive agents.
Keywords: Drug-Related Side Effects and Adverse Reactions; Protein-Losing Enteropathies; olmesartan medoxomil; průjem; enterokolitida; lidé; Olmesartan Medoxomil; nežádoucí účinky léčiv; angiotensin II; Enterocolitis; Diarrhea; exsudativní enteropatie; Angiotensin II; Humans